2019
DOI: 10.36067/jbis.v1i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Diamond fraud analysis in detecting financial statement fraud

Abstract: This study aims to analyze the influence of variable pressure proxied by financial stability, personal financial need, financial targets, external pressure, the opportunity proxied by nature of the industry, ineffective monitoring, rationalization, and capability of the financial statement fraud. The sample used 72 manufactured company listing on the Indonesia Stock Exchange during the 2014-2017 period. Multiple linear regression test is used to test the influence of the independent variable on the depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
7
1
1
Order By: Relevance
“…The results of this study are in line with research conducted by (Herdiana and Sari, 2018), (Ayuningrum, Murni and Astuti, 2021), (Paramitha, Frederica and Iskandar, 2022), stating that financial targets effect on fraudulent financial statements. While according to (Annisya, Lindrianasari and Asmaranti, 2016), (Saputra and Kesumaningrum, 2017), (Diansari and Wijaya, 2018) state financial targets has no effect on fraudulent financial statements.…”
Section: Effect Of Financial Targets On Fraudulent Financial Statementsmentioning
confidence: 99%
“…The results of this study are in line with research conducted by (Herdiana and Sari, 2018), (Ayuningrum, Murni and Astuti, 2021), (Paramitha, Frederica and Iskandar, 2022), stating that financial targets effect on fraudulent financial statements. While according to (Annisya, Lindrianasari and Asmaranti, 2016), (Saputra and Kesumaningrum, 2017), (Diansari and Wijaya, 2018) state financial targets has no effect on fraudulent financial statements.…”
Section: Effect Of Financial Targets On Fraudulent Financial Statementsmentioning
confidence: 99%
“…Laporan keuangan memberikan gambaran tentang informasi akuntansi yang menghubungkan kegiatan ekonomi perusahaan dan pengguna laporan keuangan. (Diansari & Wijaya, 2019). Setiap daerah baik kota maupun kabupaten pasti membutuhkan investor untuk menyediakan dana tambahan untuk keberlanjutan kelangsungan hidup dan perkembangan suatu daerah.…”
Section: Pendahuluanunclassified
“…In this study, a gap was found where the results of research that tested the fraud diamond factor that could affect financial statement fraud, such as research conducted by Diansari & Wijaya (2019), Yesiariani (2017), andSaputra (2017). Research on the relationship between financial stability has a positive effect on financial statement fraud (Kurniawan, 2017), while according to Norbarani (2012) there is no significant relationship between financial stability and financial statement fraud.…”
Section: Introductionmentioning
confidence: 96%